Evaluating mobile harm reduction services for youth and young adults - Yeo, Ellis J.; Hausman, Elizabeth; Noyes, Elizabeth; Chatterjee, Avik (Frontiers in Public Health, 2024)
The adolescent and young adult (AYA) population has experienced an increase in both emergency room visits and deaths related to substance use. However, AYA are less likely to engage in existing addiction treatment infrastructure. A youth-specific mobile harm reduction program has the potential to reduce substance-related morbidity and mortality including infections, overdose, and death. Launched in 2019, the Community Care in Reach AYA pilot program seeks to address the difference in patterns of substance use between AYA and adults. The results of this evaluation suggest the importance of a youth-oriented program in increasing AYA engagement with harm reduction.